Work Accidents Analysis in Lathe Workshop - JSA with FMEA Approach: Analisis Kecelakaan Kerja di Bengkel Bubut - JSA dengan Pendekatan FMEA - Himam, Muhammad Tauhid; Widodo, Edi (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the risk levels and potential for work accidents in manufacturing processes involving heavy equipment like lathes, which often lead to accidents due to non-compliance with safety regulations. Employing job safety analysis (JSA), the research aims to minimize accidents by assessing risk levels and proposing comprehensive Personal Protective Equipment (PPE) usage for workers. Results reveal that the welding process's failure mode severity is rated at 2, while lathe-related accidents, particularly exposure to debris, have the highest occurrence and effect analysis at 6. Limited PPE availability contributes to a low failure mode detection and effect analysis score of 7. This study underscores the critical need for implementing stringent safety measures to mitigate workplace accidents in manufacturing settings. Highlights : Comprehensive assessment: Utilizing job safety analysis (JSA), the study provides a detailed evaluation of potential work accidents in manufacturing processes, focusing on heavy equipment usage. Risk mitigation: The research emphasizes the importance of implementing stringent safety measures, including the complete utilization of Personal Protective Equipment (PPE), to minimize the occurrence of workplace accidents. Importance of compliance: Non-compliance with safety regulations, particularly regarding the use of PPE and adherence to K3 regulations, significantly increases the risk of work accidents, leading to disruptions in production processes. Keywords: Workplace Safety, Manufacturing, Job Safety Analysis, Personal Protective Equipment, Risk Assessment